The Regulation of Legal Protection for Poor Communities Toward Justice in Indonesia and the Netherlands - Partogi Sihombing , Januardo Sulung; Saraswati , Retno; Yunanto, Yunanto; Turymshayeva , Arida (Lembaga Contrarius Indonesia, 2024)
Poor people often have difficulty accessing legal aid in court. In the criminal, civil, and state administrative justice systems, providing legal assistance to the poor is essential for achieving justice. This research aims to illustrate how legal aid, provided by advocates, can transform the reality of justice for impoverished individuals. This study uses normative legal research, providing a descriptive account through a legal framework encompassing legal aid, the judiciary, judicial authority, and advocates. The research also uses a conceptual approach to human rights and justice, aiming to establish an ideal model of legal protection for people experiencing poverty. The research results demonstrate that providing legal assistance to people experiencing poverty not only shields the community from arbitrary actions by the authorities that violate the law but also fosters order and peace, ensuring the community receives justice. However, in Indonesia, establishing criteria for the impoverished remains challenging; structurally, the institutional budget is insufficient; culturally, the impoverished often harbor misconceptions and skepticism about the quality and affordability of legal aid. Meanwhile, in the Netherlands, providing legal protection is carried out through legal assistance, with the consideration of offering toevoeging and consideration of legal assistance based on people's salaries. Based on the number of cases for which assistance is provided, the results and public awareness are much better, although not optimal. The concept of providing legal aid must also be directed towards a responsive and structural type, combined with the concept of access to law and justice. Budgetary policies or rules must be regulated concretely and balanced from the individual validation stage, selecting the type of service and appointing a lawyer for evaluation.